TOWARD A MENTALISTIC ACCOUNT OF EARLY PSYCHOLOGICAL REASONING - Luo, Yuyan (2010)
Recent investigations of early psychological understanding have revealed three key findings. First, young infants attribute goals and dispositions to any entity they perceive as an agent, whether human or non-human. Second, when interpreting an agent’s actions in a scene, young infants take into account the agent’s representation of the scene, even if this representation is less complete than their own. Third, at least by the second year of life, infants recognize that agents can hold false beliefs about a scene. Together, these findings support a system-based, mentalistic account of early psychological reasoning.